2021
DOI: 10.1002/tpg2.20087
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association mapping identifies novel loci underlying fire blight resistance in apple

Abstract: Fire blight, caused by epiphytotic gram-negative bacteria Erwinia amylovora, is the most destructive bacterial disease of apple (Malus spp.). Genetic mechanisms of fire blight resistance have mainly been studied using traditional biparental quantitative trait loci (QTL) mapping approaches. Here, we use large-scale historic shoot and blossom fire blight data collected over multiple years and genotyping-by-sequencing (GBS) markers to identify significant marker-trait associations in a diverse set of 566 apple [M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 81 publications
0
7
1
Order By: Relevance
“…Genome-wide association studies (GWAS) can use these millions of SNPs as molecular markers to screen many accessions simultaneously without needing to construct segregating populations in advance ( Buckler and Thornsberry, 2002 ; Flint-Garcia et al, 2003 ; Yu et al, 2006 ; Wang et al, 2016 ; Zhang et al, 2019 ). For instance, Thapa et al (2021) identified 23 and 38 QTNs associated with shoot and blossom blight resistance, respectively, using GBS markers in 273 apple accessions, while Jing et al (2021) identified 18 QTNs related to Sclerotinia stem rot resistance in soybean. Thus, GWAS is an efficient tool for QTN identification in natural populations with high-quality SNPs to overcome the shortcomings of bi-parental QTL mapping ( Zhang et al, 2019 ) and has great potential for discovering interrelationships among complex traits conditioned by multiple genes/alleles ( Buckler and Thornsberry, 2002 ; Yu et al, 2006 ; Hyun et al, 2021 ; Thapa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genome-wide association studies (GWAS) can use these millions of SNPs as molecular markers to screen many accessions simultaneously without needing to construct segregating populations in advance ( Buckler and Thornsberry, 2002 ; Flint-Garcia et al, 2003 ; Yu et al, 2006 ; Wang et al, 2016 ; Zhang et al, 2019 ). For instance, Thapa et al (2021) identified 23 and 38 QTNs associated with shoot and blossom blight resistance, respectively, using GBS markers in 273 apple accessions, while Jing et al (2021) identified 18 QTNs related to Sclerotinia stem rot resistance in soybean. Thus, GWAS is an efficient tool for QTN identification in natural populations with high-quality SNPs to overcome the shortcomings of bi-parental QTL mapping ( Zhang et al, 2019 ) and has great potential for discovering interrelationships among complex traits conditioned by multiple genes/alleles ( Buckler and Thornsberry, 2002 ; Yu et al, 2006 ; Hyun et al, 2021 ; Thapa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Thapa et al (2021) identified 23 and 38 QTNs associated with shoot and blossom blight resistance, respectively, using GBS markers in 273 apple accessions, while Jing et al (2021) identified 18 QTNs related to Sclerotinia stem rot resistance in soybean. Thus, GWAS is an efficient tool for QTN identification in natural populations with high-quality SNPs to overcome the shortcomings of bi-parental QTL mapping ( Zhang et al, 2019 ) and has great potential for discovering interrelationships among complex traits conditioned by multiple genes/alleles ( Buckler and Thornsberry, 2002 ; Yu et al, 2006 ; Hyun et al, 2021 ; Thapa et al, 2021 ). However, no GWAS studies have been undertaken to detect QTNs associated with TBW resistance in tobacco.…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, mostly a collection of diverse individual genotypes or diverse populations that are unrelated and can capture all possible recombination events are used. Such a population structure results in increased mapping resolution, improved transferability from one family to another, and increased discovery of SNPs across the whole genome ( Kumar et al., 2012a ; Peace et al., 2019 ; Thapa et al., 2021 ).…”
Section: Fruit Growthmentioning
confidence: 99%
“…Finally, markers controlling harvest date were co-localized with the coding region of a NAC transcription factor that regulates fruit ripening and maturity in apple ( Larsen et al., 2019 ). Recently, a genome-wide methods was applied to study other physiological traits such as fruit texture ( Di Guardo et al., 2017 ), fire blight resistance loci ( Thapa et al., 2021 ), scab resistance ( McClure et al., 2018 ), and flesh browning ( Kunihisa et al., 2021 ). Findings of these studies indicate that genome-wide techniques can facilitate increased mapping resolution, increased detection of multiple alleles at the same locus, and a high number of SNPs that adequately cover the whole genome.…”
Section: Fruit Growthmentioning
confidence: 99%
“…Diverse set of 566 apple accessions identified significant marker trait associations for fire blight of apple caused by Erwinia amylovora . A total of 23 and 38 MTAs significantly (p<.001) associated with shoot and blossom blight resistance, respectively ( Thapa et al., 2021 ). GWAS based on 195 accessions and 145,456 genome-wide SNPs identified five SNPs and six candidate genes significantly associated with gummosis disease resistance in peach ( Li et al., 2021b ).…”
Section: Other Key Cropsmentioning
confidence: 99%